2012
DOI: 10.1016/j.engstruct.2012.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Energy flow in progressive collapse of steel framed buildings

Abstract: This paper provides the methodology for an energy-based progressive collapse assessment of multistory buildings. The progressive collapse of steel-framed buildings is analyzed based on an energy flow perspective. The energy based assessment of structural members is introduced, and compared with conventional force and deformation approaches discussed in the literature. Consecutively, the advantages of energy flow analysis in interpretation of extreme dynamic events are discussed. On the global level, a building… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 28 publications
1
32
0
2
Order By: Relevance
“…Also, metallic foams are renowned for their compressibility of 0.9 engineering strain or more [5], giving them extraordinary energy dissipation capacity [2], which is instrumental in arresting extreme dynamic events because it dissipates the kinetic energy. Once the kinetic energy is removed completely, the system reaches a stable state [6,7]. Energy dissipation capacity has been experimentally observed in metallic foams even under high strain rates [8].…”
mentioning
confidence: 96%
“…Also, metallic foams are renowned for their compressibility of 0.9 engineering strain or more [5], giving them extraordinary energy dissipation capacity [2], which is instrumental in arresting extreme dynamic events because it dissipates the kinetic energy. Once the kinetic energy is removed completely, the system reaches a stable state [6,7]. Energy dissipation capacity has been experimentally observed in metallic foams even under high strain rates [8].…”
mentioning
confidence: 96%
“…Dissipation of vibrational kinetic energy under dynamic loading [20][21][22] is essential for the attenuation of unwanted vibrations and oscillations that can lead to premature failure. Although polymeric materials typically offer excellent damping properties, they are not feasible in high temperature environments and there is a need for non-polymeric materials that can dampen vibrations at high operating temperatures without the use of a damping fluid.…”
mentioning
confidence: 99%
“…They concluded that both material and geometric nonlinearities should be accounted for, and that catenary action improves the overall structural behaviour. Kwasniewski (2010) and Szyniszewski and Krauthammer (2012) performed nonlinear dynamic analysis (both material and geometric nonlinearities included) in 3D frames incorporating the slab. Kwasniewski (2010) and Szyniszewski and Krauthammer (2012) performed nonlinear dynamic analysis (both material and geometric nonlinearities included) in 3D frames incorporating the slab.…”
Section: Introductionmentioning
confidence: 99%